2012
DOI: 10.1111/j.1365-2966.2012.21767.x
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal of molecular clouds by ionizing radiation

Abstract: Feedback from massive stars is believed to be a key element in the evolution of molecular clouds. We use high‐resolution 3D smoothed particle hydrodynamics simulations to explore the dynamical effects of a single O7 star‐emitting ionizing photons at 1049 s−1 and located at the centre of a molecular cloud with mass 104 M⊙ and radius 6.4 pc; we also perform comparison simulations in which the ionizing star is removed. The initial internal structure of the cloud is characterized by its fractal dimension, which we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
220
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(234 citation statements)
references
References 97 publications
14
220
0
Order By: Relevance
“…The importance of bubbles was highlighted in recent work by and Lee et al (2012), who find that the feedback energy from expanding bubbles in star-forming complexes is a major driver of turbulence in the ISM of the inner Milky Way, possibly more important than that from supernovae. Both the triggering and quenching of star formation by massive stellar feedback are observed in smoothed particle hydrodynamics simulations by Dale et al (2005Dale et al ( , 2007 and Walch et al (2012).…”
Section: Feedback From Massive Stars and Clustersmentioning
confidence: 99%
“…The importance of bubbles was highlighted in recent work by and Lee et al (2012), who find that the feedback energy from expanding bubbles in star-forming complexes is a major driver of turbulence in the ISM of the inner Milky Way, possibly more important than that from supernovae. Both the triggering and quenching of star formation by massive stellar feedback are observed in smoothed particle hydrodynamics simulations by Dale et al (2005Dale et al ( , 2007 and Walch et al (2012).…”
Section: Feedback From Massive Stars and Clustersmentioning
confidence: 99%
“…Dale et al (2012Dale et al ( , 2013 did extensive three-dimensional simulations of star cluster formation with ionization or stellar wind feedback and showed that the effects of photoionization and stellar winds are limited in quenching the star formation in massive molecular clouds (see also Walch et al 2012). Diaz-Miller et al (1998) calculated the steady-state structures of HII regions and pointed out that the photodissociation of hydrogen molecules due to far-ultraviolet (FUV) photons is much more important than photoionization due to UV photons for the destruction of molecular clouds.…”
Section: Quenching Of Star Formation In Molecular Cloudsmentioning
confidence: 99%
“…Since treating precisely the dense gas and the supernova correlation implies resolving not only the star formation well but also following the detailed star trajectories, this constitutes a very difficult task, that renders prescriptions like the one we are using unavoidable. More generally, other sources of feedback such as HII radiation and stellar winds should be considered as well (Walch et al 2012;Dale et al 2013Dale et al , 2014Geen et al 2015Geen et al , 2016.…”
Section: Supernova Feedbackmentioning
confidence: 99%